2012
DOI: 10.3174/ajnr.a3125
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral White Matter Disruption in Creutzfeldt-Jakob Disease

Abstract: BACKGROUND AND PURPOSE:Human prion diseases are known to cause gray matter degeneration in specific cerebral structures, but evidence for white matter involvement is scarce. We used DTI to test the hypothesis that white matter integrity is disrupted in human CJD during the early stages of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
24
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 39 publications
4
24
2
Order By: Relevance
“…Recently this technique was applied to study 21 patients with E200K genetic prion disease (Lee et al , 2012) and showed reduced fractional anisotropy in many important white matter pathways and suggested that reduced fractional anisotropy was associated with a functional disconnection syndrome (Lee et al , 2012). Whether white matter is primarily affected in CJD or involved secondarily through involvement of cell bodies within the grey matter remains unclear (Kucharczyk and Bergeron, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Recently this technique was applied to study 21 patients with E200K genetic prion disease (Lee et al , 2012) and showed reduced fractional anisotropy in many important white matter pathways and suggested that reduced fractional anisotropy was associated with a functional disconnection syndrome (Lee et al , 2012). Whether white matter is primarily affected in CJD or involved secondarily through involvement of cell bodies within the grey matter remains unclear (Kucharczyk and Bergeron, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Significant reductions of fractional anisotropy in patients with CJD in distinct and functionally relevant white matter pathways (including corticospinal, internal capsule, external capsule, fornix, and posterior thalamic radiation) correlate with progressive leukoencephalopathy and, more importantly, provide diagnostic criteria early in the disease course. 28 The disease stage also has a significant impact on the nature of the MRI pattern. DWI is considered superior to any other MRI sequence in the early stages of CJD.…”
mentioning
confidence: 99%
“…This approach allowed us to have a more homogeneous cohort and minimize the Clinical Dementia Rating Scale SD across the patient group. Nine individuals with the 6-OPRI mutation were studied (6-OPRI group: mean age, 38.1 Ϯ 3.6 years; median MiniMental State Examination, 19 [range [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]; all codon 129MM). Sixteen healthy volunteers with no history of neurologic disorder were included (Controls group: mean age, 37.1 Ϯ 10.7 years; all Mini-Mental State Examination, 30); Table 1.…”
Section: Patientsmentioning
confidence: 99%
“…These tools have not been applied in IPD, except for patients with the E200K mutation. [16][17][18] We performed VBM, MTR-VBA, and MD-VBA in a cohort of patients with IPD who have the 6-OPRI mutation, some of whom were previously studied with alternative methods. 12,13 We hypothesized that this multiparametric approach would localize brain abnormalities corresponding to known clinical symptoms and neuropsychological deficits and, further, that MTR and MD would quantify microstructural changes even in areas without significant volume loss on VBM.…”
mentioning
confidence: 99%